2022
DOI: 10.1177/21501319221121464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Peer Led Chronic Pain Self-Management Program in a Rural Population

Abstract: Background: The Chronic Pain Self-Management Program is an evidence-based intervention that has been shown to be efficacious in reducing symptoms of chronic pain. However, there is a paucity of research examining CPSMP in a predominantly rural population. The purpose was to evaluate patient-reported outcomes of in-person peer-led CPSMP workshops offered in a rural region in 2018 and 2019. Methods: Participants were surveyed at baseline and 6 months post-workshop. Descriptive statistics were used to describe ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…While a nationwide evaluation of the in-person CDSME workshops did not examine differences in education between completers and noncompleters, a Canadian study by McGowan found that education level was not a significant factor for completing in-person self-management workshops [ 13 ]. Our in-person workshop findings also indicated no significant difference in education level between completers and noncompleters [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 82%
“…While a nationwide evaluation of the in-person CDSME workshops did not examine differences in education between completers and noncompleters, a Canadian study by McGowan found that education level was not a significant factor for completing in-person self-management workshops [ 13 ]. Our in-person workshop findings also indicated no significant difference in education level between completers and noncompleters [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 82%
“…The mean pre-post changes in participant reported outcomes were similar to those observed for participants in the in-person workshops offered in the same region prior to 2020. 10 In a study of remote delivery of CPSMP using mailed toolkit with phone support from July-December 2020, Sheth et al found significant improvements in depression (PHQ-8), pain (visual analogue scale) and chronic disease self-efficacy at 6 weeks. 9 Mean changes for comparable measures (PHQ-8 and pain) were larger than what we observed (mean difference for PHQ-8 was −1.42 and pain was −5.94 compared with −1.03 and −0.61, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In-person completion rates were 73% in the studied region prior to the pandemic. 10 This finding could be attributed to secular trends, such as the pandemic, as well as the limited availability of low-latency, high-speed internet in parts of our region that makes staying connected to a 2½-hour long videoconference session difficult. But, it may also be related to the imperfect transferability of a program designed for in-person to a videoconference platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…kann das Schmerzselbstmanagement bedeutsam verbessern. Die Teilnehmenden (N = 327), die mehrheitlich über 65 Jahre alt waren, wiesen auch sechs Monate nach Programmende noch eine Verbesserung der schmerzbezogenen Selbstwirksamkeit, der schmerzbedingten Beeinträchtigung und der Depressivität auf, und zwar unabhängig vom Alter [45]. Dabei muss berücksichtigt werden, dass die Teilnehmer gesundheitlich eher gering beeinträchtigt waren: So stuften 57 % ihre gesundheitliche Verfassung als "gut" oder besser ein.…”
Section: Psychologische Interventionenunclassified